Atopic Dermatitis in Individuals of Asian and African Ancestry: A Scoping Systematic Review - Chiedu Ufodiama; Blessing Fabowale-Makinde; Christine Kleyn (Mattioli1885, 2023)
Introduction: Atopic Dermatitis (AD) affects individuals from all ethnicities and backgrounds. It has the highest global disease burden of dermatoses. There is a widely held belief that the presentation of AD is not described well in individuals with non-European ancestry in peer-reviewed literature. However, to our knowledge, this has not been investigated previously Objective: To quantify the number of peer-reviewed literature describing the appearance of clinical features of AD in non-European ancestry, particularly those originating from the Asian and African continents. Methods: A systematic scoping review between December 2020 and January 2021 was performed to quantify the number of studies describing AD in individuals of African and Asian ancestry. Reuslts: Sixteen studies were identified. None of the studies provided a clear description of AD in our population groups. Two studies described features of lichen planus like-AD in African American individuals. All studies reported on observed clinical features of AD. Conclusions: The review confirmed a lack of literature describing AD in populations of non-European heritage. It should encourage authors to make a deliberate effort to describe the appearance of clinical features of AD to enable understanding of  how they may differentiate in individuals originating from different parts of the globe.